Irrigation, agriculture and social development - Hooja, Rakesh (ed.) (New Delhi, 1997)
The book on irrigation drainage and social development is an outgrowth of the workshop on irrigation, drainage and social development: myths and realities organised by RATED project. The bulk of the papers in this book have been selected from those presented in the workshop.
Keywords: Agricultural development